In vitro effects of green tea (Camellia sinensis) aqueous extract on sperm quality: Mitigating oxidative stress and sperm DNA fragmentation in freeze-dried human spermatozoa - Narges Joulaeerad; Homa Hajimehdipoor; Mohammad Hossein Heidari; Mahsa Kazemi; Hamid Nazarian; Zahra Shams Mofarahe; Latif Gachkar; Marefat Ghaffari Novin (Clinical and Experimental Reproductive Medicine, 2026)
Objective: Freeze-drying is a promising method for the long-term preservation of sperm; however, it often leads to increased oxidative stress. Green tea (Camellia sinensis [L.] Kuntze) contains polyphenols known for their antioxidant properties. This study aimed to evaluate the in vitro effects of green tea aqueous extract (GTE) on oxidative stress markers and sperm DNA fragmentation (SDF) in freeze-dried human sperm.Methods: Ten normal semen samples were collected from men aged 20 to 45 years and divided into three groups: conventionally cryopreserved (A), freeze-dried (B), and freeze-dried with pre-incubation in GTE (C). In group C, samples were incubated with 1 mL of GTE at a concentration of 40 μg/mL for 30 minutes prior to freeze-drying. Oxidative stress markers and SDF were assessed 1 month post-preservation, following thawing in group A and rehydration in groups B and C.Results: Freeze-drying resulted in less DNA damage to sperm compared to cryopreservation (p=0.005). Relative to cryopreservation, incubation with GTE significantly reduced intracellular reactive oxygen species levels (p